Engineered fully human single‐chain monoclonal antibodies to PIM2 kinase - Kanasap Kaewchim (2022)
Proviral integration site of Moloney virus‐2 (PIM2) is overexpressed in multiple human cancer cells and high level is related to poor prognosis; thus, PIM2 kinase is a rational target of anti-cancer therapeutics. Several chemical inhibitors targeting PIMs/PIM2 or their downstream signaling molecules have been developed for treatment of different cancers. However, their off‐target toxicity is common in clinical trials, so they could not be advanced to official approval for clinical application. Here, we produced human single‐chain antibody fragments (HuscFvs) to PIM2 by using phage display library, which was constructed in a way that a portion of phages in the library carried HuscFvs against human own proteins on their surface with the respective antibody genes in the phage genome. Bacterial derived‐recombinant PIM2 (rPIM2) was used as an antigenic bait to fish out the rPIM2‐bound phages from the library. Three E. coli clones transfected with the HuscFv genes derived from the rPIM2‐bound phages expressed HuscFvs that bound also to native PIM2 from cancer cells. The HuscFvs presumptively interact with the PIM2 at the ATP binding pocket and kinase active loop. They were as effective as small chemical drug inhibitor (AZD1208, which is an ATP competitive inhibitor of all PIM isoforms for ex vivo use) in inhibiting PIM kinase activity. The HuscFvs should be engineered into a cell‐penetrating format and tested further towards clinical application as a novel and safe pan‐anti‐cancer therapeutics.